Integrated analysis of copy number and loss of heterozygosity in primary breast carcinomas using high-density SNP array - Ching, H.C.; Naidu, R.; Seong, M.K.; Har, Y.C.; Taib, N.A. (Athens, 2011)
Breast cancer is a heterogeneous disease, marked by extensive chromosomal aberrations. In this study, we aimed to explicate the underlying chromosomal copy number (CN) alterations and loss of heterozygosity (LOH) implicated in a cohort of Malaysian hospital-based primary breast carcinoma samples using a single nucleotide polymorphism (SNP) array platform. The analysis was conducted by hybridizing the extracted DNA of 70 primary breast carcinomas and 37 normal peripheral blood samples to the Affymetrix 250K Sty SNP arrays. Locus-specific CN aberrations and LOH were statistically summarized using the binary segmentation algorithm and hidden Markov model. Selected genes from the SNP array analysis were also validated using quantitative real-time PCR. The merging of CN and LOH data fabricated distinctive integrated alteration profiles, which were comprised of finely demarcated minimal sites of aberrations. The most prevalent gains (≥30%) were detected at the 8q arm: 8q23.1, 8q23.3, 8q24.11, 8q24.13, 8q24.21, 8q24.22, 8q24.23 and 8q24.3, whilst the most ubiquitous losses (≥20%) were noted at the 8p12, 8p21.1, 8p21.2, 8p21.1-p21.2, 8p21.3, 8p22, 8p23.1, 8p23.1‑p23.2, 8p23.3, 17p11.2, 17p12, 17p11.2-p12, 17p13.1 and 17p13.2 regions. Copy-neutral LOH was characterized as the most prevailing LOH event, in which the most frequent distributions (≥30%) were revealed at 3p21.31, 5q33.2, 12q24.12, 12q24.12‑q24.13 and 14q23.1. These findings offer compre-hensive genome-wide views on breast cancer genomic changes, where the most recurrent gain, loss and copy-neutral LOH events were harboured within the 8q24.21, 8p21.1 and 14q23.1 loci, respectively. This will facilitate the uncovering of true driver genes pertinent to breast cancer biology and the develop-ment of prospective therapeutics.